Game form misconceptions are not necessary for a willingness-to-pay vs. willingness-to-accept gap - Björn Bartling; Florian Engl; Roberto Weber (University of Zurich, Department of Economics, 2015)
Cason and Plott (2014) show that subjects' misconception about the incentive properties of the Becker-DeGroot-Marschak (BDM) value elicitation procedure can generate data patterns that look like - and might thus be misinterpreted as evidence for - preferences constructed from endowments or reference points. We test whether game form misconceptions are necessary to produce willingness-to-pay (WTP) vs. willingness-to-accept (WTA) gaps in a valuation experiment in which subjects are randomly assigned to the role of either buyer or seller. We employ a design that allows us to identify whether a subject understood the incentive properties of a price-list version of the BDM mechanism. We find a robust WTP-WTA gap, even among subjects whose elicited valuations for a good of induced and known monetary value and whose ability to identify the payoffs resulting from their choices indicate an understanding of the incentive properties of the BDM mechanism. We conclude that game form misconceptions are not a necessary condition for the emergence of WTP-WTA gaps.
Keywords: C91; D03; 330; WTP-WTA gap; game from misconception; BDM mechanism; endowment effect; experimental methods; highly replicable laboratory environment